Legal Certainty of the Role of Notaries in Electronic General Meetings of Shareholders of Limited Liability Companies in an Effort to Support the Asean Economic Community - Biner Sihotang (Journal of Law, Politic and Humanities, 2025)
Technological advances and in an effort to improve services to the community, a concept has been introduced in the world of public services that uses Information and Communication Technology (ICT) such as the General Meeting of Shareholders (GMS) of Limited Liability Companies which can be conducted conventionally or via teleconference or videoconference, thus demanding the role of Notaries in an effort to provide legal certainty for the implementation of the General Meeting of Shareholders (GMS) of Limited Liability Companies. The problem in this study is how is the legal certainty of the role of notaries in general meetings of shareholders of limited liability companies electronically in an effort to support the ASEAN Economic Community? This study is a normative legal study using secondary data and analyzed descriptively. The results of the study show that the legal certainty of the role of notaries in general meetings of shareholders of limited liability companies electronically in an effort to support the ASEAN Economic Community can be carried out by playing a role in organizing electronic certification as a registration authority (RA) that verifies data and the identity of users of electronic signatures, for example in the case of General Meetings of Shareholders (GMS) of Limited Liability Companies which can be conducted conventionally or via teleconference or videoconference. If done by teleconference or videoconference, then everything that is discussed that occurs must be recorded and stored in a storage medium for that purpose as an Electronic Document and must be stored by the Notary as part of the Minutes of the Deed, also as part of the Notary Protocol, which at some point if needed, for example for evidence in court can be reopened. However, the Notary's obligation is to continue to make the Minutes of the Deed in the form of ordinary paper, which has been done so far.